Engineering interfacial migration by collective tuning of adhesion anisotropy and stiffness. (May 2018) - George, Edna; Barai, Amlan; Shirke, Pallavi; Majumder, Abhijit; Sen, Shamik
Graphical abstract: Abstract: Interfacial migration is central to multiple processes including morphogenesis and wound healing. However, the sensitivity of interfacial migration to properties of the interfacial microenvironment has not been adequately explored. Here, we address this question by tracking motility of 3T3 fibroblasts at the interface of two hydrogels. By sandwiching cells between two adhesive gels (composed of methacrylated gelatin) or between an adhesive and a non-adhesive gel (composed of gellan), we show that cells are more motile in case of the latter. By tuning the bulk stiffness of the gellan gel, we then show that motility is tuned in a stiffness-dependent manner. Fastest motility observed in case of the stiffest gel was associated with increased cell height, suggestive of stiffness-mediated cytoskeletal assembly. Inhibition of cell motility by contractile agonists and actin depolymerizing drugs is indicative of a mode of migration wherein cells combine contractile tractions exerted at their base and actin-based pushing forces on the top surface to propel themselves forward. Together, our results suggest that dorso-ventral adhesion anisotropy and stiffness can be collectively tuned to engineer interfacial migration. Statement of Significance: It is increasingly understood that cells migrate in vivo through confining spaces which typically occur as pores in the matrix and through naturally occurring interfaces that exist between neighbouring ECM fibers, or between the stroma and the vasculature. Such interfaces are also created when treating wounds on the skin surface by covering the wounds with adhesives. How multiple cues impact interfacial migration has not been adequately addressed. By studying cell migratory behaviour at the interface of two hydrogel substrates, we identify adhesivity and stiffness as two critical factors that can be tuned to maximize cell migration. We foresee a potential use of this knowledge in the design of tissue adhesives for wound healing applications.